2016
DOI: 10.1007/s10754-016-9189-1
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance coverage and self-reported health: new estimates from the NLSY97

Abstract: This paper provides new estimates of the relationship between health insurance coverage and health status of young adults using the confidential version of the National Longitudinal Survey of Youth, 1997 Cohort (NLSY97). Using a regression discontinuity design, I find that approximately 6 % of young adults lose their health insurance coverage once they turn 19. However, in contrast to the findings from the recent literature, the effect of this discrete change in health insurance coverage on self-reported healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…32 Thus, SROH is regarded as a practical and easily interpreted measure to assess inequalities in the oral health of a population. 11,12,33,34 We confirmed the same patterns of the outcome variable through a sensitivity analysis and robustness check. The supplemental table (eTable 1) shows the results separating "poor" versus "very poor".…”
Section: Discussionsupporting
confidence: 61%
“…32 Thus, SROH is regarded as a practical and easily interpreted measure to assess inequalities in the oral health of a population. 11,12,33,34 We confirmed the same patterns of the outcome variable through a sensitivity analysis and robustness check. The supplemental table (eTable 1) shows the results separating "poor" versus "very poor".…”
Section: Discussionsupporting
confidence: 61%
“…The effect of health insurance coverage on self-reported health has been investigated in different countries with no compulsory medical insurance and no publicly provided universal health coverage, see for example Simon, Soni, and Cawley (2017), Sommers, Maylone, Blendon, Orav, andEpstein (2017), Baicker, Taubman, Allen, Bernstein, Gruber, Newhouse, Schneider, Wright, Zaslavsky, andFinkelstein (2013), Yörük (2016) and Cardella and Depew (2014) for the U.S. and King, Gakidou, Imai, Lakin, Moore, Nall, (2009) for Mexico). Most of these studies find a significant positive effect of insurance coverage on self-reported health.…”
Section: Applicationmentioning
confidence: 99%
“…Regarding the causal effect of health insurance on health, a review concluded that the observed correlation between insurance and good health might be driven by other factors (6). Two current studies indicated that the effect relied on the health insurance coverage (7, 8). Also, health insurance had some limitations.…”
Section: Introductionmentioning
confidence: 98%